2018
DOI: 10.5194/dwes-11-87-2018
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the start-up period of a full-scale drinking water biofilter provides guidance for optimization

Abstract: Abstract. The use of biofilters to produce drinking water from anaerobic groundwater is widespread in some European countries. A major disadvantage of biofilters is the long start-up period required for virgin filter medium to become fully functional. Although individual aspects of biofilter start-up have previously been investigated, no comprehensive study in full scale using inherent inoculation has previously been documented. A thorough investigation of a full-scale drinking water biofilter was carried out … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
2
8
1
Order By: Relevance
“…These increases in redox potential likely resulted from the oxidation of Fe and NH 4 (Mouchet, 1992;Stumm & Morgan, 1996;Tekerlekopoulou & Vayenas, 2008). Therefore, the PHREEQC model is consistent with observations in the literature, which have found that Fe and NH 4 are oxidized closer to the surface of the biofilter, while Mn is oxidized at depth Cheng, Nengzi, Xu, Guo, & Yu, 2017;Ramsay et al, 2018;Tekerlekopoulou & Vayenas, 2008).…”
Section: Predicting Mn Mineral Formation Using Phreeqcsupporting
confidence: 84%
See 2 more Smart Citations
“…These increases in redox potential likely resulted from the oxidation of Fe and NH 4 (Mouchet, 1992;Stumm & Morgan, 1996;Tekerlekopoulou & Vayenas, 2008). Therefore, the PHREEQC model is consistent with observations in the literature, which have found that Fe and NH 4 are oxidized closer to the surface of the biofilter, while Mn is oxidized at depth Cheng, Nengzi, Xu, Guo, & Yu, 2017;Ramsay et al, 2018;Tekerlekopoulou & Vayenas, 2008).…”
Section: Predicting Mn Mineral Formation Using Phreeqcsupporting
confidence: 84%
“…These results suggest that Fe would be rapidly oxidized by oxygen and precipitate in the upper layers of the biofilters. In groundwater biofilters with aeration, Fe is often removed at the top of the biofilter immediately when the filter is put into service Ramsay et al, 2018). The additional information provided by this model over the Pourbaix diagram is useful for analyzing biofilters.…”
Section: Predicting Fe Mineral Formation Using Phreeqcmentioning
confidence: 99%
See 1 more Smart Citation
“…More important, functioning of a filter may suddenly be disrupted due to a number of reasons, including mechanical filter breaches, filter media replacements, and start-up of new filters. During such episodes of disrupted filtering, Mn concentrations in drinking water sharply increase, typically between 10-and 100-fold, and stay elevated for long periods, from several months to more than a year, before the removal of Mn is reestablished (Breda et al 2017;Bruins et al 2014;Gouzinis et al 1998;Ramsay et al 2018). Exposure to high levels of Mn through drinking water supplies based on simple-treated groundwater is therefore mainly governed by episodic water treatment failure.…”
Section: Introductionmentioning
confidence: 99%
“…(b) Mn versus NH 4 removal (percentage) over time (days 11, 27, 35, 39, 43, 67 and approximately 4 years) calculated based on the concentration of each substance in water samples collected over 20 cm depth intervals in relation to the inlet concentrations at DWTP9. All data were retrieved from Ramsay et al (2018) with the exception of observations at 4 years. Please refer to the online version of this paper to see this figure in colour: http://dx.doi.org/10.2166/wqrj.2019.006.…”
Section: Effect Of the Biological Inhibitor Nan 3 On The Mn R Cmentioning
confidence: 99%